2022
DOI: 10.3389/fpls.2022.958350
|View full text |Cite|
|
Sign up to set email alerts
|

Will epigenetics be a key player in crop breeding?

Abstract: If food and feed production are to keep up with world demand in the face of climate change, continued progress in understanding and utilizing both genetic and epigenetic sources of crop variation is necessary. Progress in plant breeding has traditionally been thought to be due to selection for spontaneous DNA sequence mutations that impart desirable phenotypes. These spontaneous mutations can expand phenotypic diversity, from which breeders can select agronomically useful traits. However, it has become clear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 219 publications
0
8
0
Order By: Relevance
“…This process also determines histone modification patterns and helps recruit repressor complexes that contain HD7ACs, DNMTs, and MBD proteins. DM, unlike DNA sequence alterations, will result in complex DM states in crossbreeding populations, but it still has the potential to create novel and desirable phenotypes that genetic variety cannot provide [ 37 , 38 ]. It was further confirmed that, because DM is linked to gene expression, alterations in the methylation of areas that influence gene expression, such as cis-elements, may result in new gene expression and a new phenotype [ 37 ].…”
Section: Mechanisms Of Plant Epigenetic Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…This process also determines histone modification patterns and helps recruit repressor complexes that contain HD7ACs, DNMTs, and MBD proteins. DM, unlike DNA sequence alterations, will result in complex DM states in crossbreeding populations, but it still has the potential to create novel and desirable phenotypes that genetic variety cannot provide [ 37 , 38 ]. It was further confirmed that, because DM is linked to gene expression, alterations in the methylation of areas that influence gene expression, such as cis-elements, may result in new gene expression and a new phenotype [ 37 ].…”
Section: Mechanisms Of Plant Epigenetic Regulationmentioning
confidence: 99%
“…In plants, chromatin remodeling complexes play an important role in the epigenetic control of gene expression, particularly in response to stress [ 37 , 72 , 134 ]. These complexes are in charge of modifying chromatin shape, impacting DNA accessibility to transcriptional machinery and regulatory proteins [ 134 ].…”
Section: Mechanisms Of Plant Epigenetic Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…TGCs may be heritable and even persist for many generations, forming epialleles (Quadrana & Colot, 2016 ; Tonosaki et al, 2022 ; van der Graaf et al, 2015 ). Such epialleles typically consist of differentially methylated loci, where cytosines at various positions are hyper- or hypomethylated as compared to the parental alleles.…”
Section: Igcs and Tgcsmentioning
confidence: 99%